2009
DOI: 10.1097/bot.0b013e318193c2f3
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery of Elbow Range of Motion After Treatment of Supracondylar and Lateral Condylar Fractures of the Distal Humerus in Children

Abstract: In the uncomplicated distal humerus supracondylar and lateral condylar fractures, it takes 5 weeks to restore original elbow ROM after removal of long arm cast without physical therapy. This information could be applied in the education material to caregivers of children with elbow injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 19 publications
5
28
0
8
Order By: Relevance
“…Improvement was seen up to 1 year post injury. The second paper showed 90% return to range of motion at 6–7 weeks post removal of cast/wires from elbow 40 . These results indicate a 3‐ to 6‐month recovery to 90% of normal for the injured child and advising parents early of this likely timeframe allows ease in ongoing management and compliance.…”
Section: Prognosismentioning
confidence: 74%
“…Improvement was seen up to 1 year post injury. The second paper showed 90% return to range of motion at 6–7 weeks post removal of cast/wires from elbow 40 . These results indicate a 3‐ to 6‐month recovery to 90% of normal for the injured child and advising parents early of this likely timeframe allows ease in ongoing management and compliance.…”
Section: Prognosismentioning
confidence: 74%
“…Previously, Wang et al 8 , in a small, retrospective case series of sixteen pediatric lateral condylar fractures, reported that the affected elbow achieved 90% of relative motion (compared with the contralateral extremity) at a mean of five weeks after cast removal. No correlation was found between the recovery of motion and the severity of the fracture, the type of treatment, or the age of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear number at which a patient can be said to have a truly successful outcome. The objective of the study was to follow improvements longitudinally and compare them among groups, with methods that had been previously used 6,8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine klinische Untersuchung 2 bis 3 Wochen später klärt den Bedarf einer Physiotherapie, die bei sehr schlechter Beweglichkeit zu diesem Zeitpunkt in diziert ist. In der Regel ist eine 90 %ige Bewegungsfähigkeit nach 10 bis 12 Wo chen zu erwarten [22]. Bis zur vollständi gen Bewegungsfreiheit dauert es jedoch oft bis zu 1 Jahr [19].…”
Section: Nachbehandlung Nach Operativer Therapieunclassified